SUWUNG: PENCARIAN KESEMPURNAAN HIDUP MASYARAKAT JAWA - amanda anyza; Listyo Yuwanto (Universitas PGRI Adi Buana Surabaya, 2023)
Suwung is a concept in Javanese spirituality (Kejawen), which shows the condition when a person experiences what is known as the highest reality. A person who has attained Suwung feels connected to God, feels peace, knows where he came from and will return, knows the meaning and purpose of his life, has self-control and is free from the bonds of the world, accepts all situations with sincerity, shows compassion, and has desires to establish harmony with other people and nature. Spiritual well-being is a psychological theory that describes how a person relates to himself, others, God, and nature as a manifestation of his own rosperous state. This research is a literature study that aims to describe the concept of Suwung in the study of spiritual well-being. The results of this literature study indicate that the concept of spiritual well-being can explain Suwung as a form of spiritual well-being in the context of Javanese society. However, because spirituality is a concept that is close to culture, the description of Suwung and its manifestations in a person’s characteristics and behavior is more specific and in line with local values and wisdom in Javanese culture.